METHODS AND CHALLENGES IN LEARNING AND TEACHING ENGLISH PRONUNCIATION - Jurayeva Komila Bahodirovna; Khudoyberdieva Oyjamol Muzaffarovna (Western European Studies, 2025)
This thesis explores the various methods and challenges associated with learning and teaching English pronunciation. The study delves into the effectiveness of traditional and modern teaching techniques, the role of technology, and the common obstacles faced by both learners and educators. Through an extensive review of literature and empirical research, the thesis aims to provide a comprehensive understanding of how pronunciation can be improved and the best practices for teaching it
Keywords: English pronunciation; teaching methods; learning challenges